Anxiety and Suicide Risk in Adolescent Students in the City of Montería, Colombia - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
The purpose of this research is to assess anxiety levels and suicide risk in a population of adolescent students from the city of Montería, Colombia. The study aims to establish whether the two variables studied have a degree of statistical association or correlation. The study was conducted in a private educational center, with a low socioeconomic status, on a sample of 156 participants randomly selected from a universe of more than 300 students. The research followed a quantitative approach with a descriptive correlational design. A total of five correlations were conducted between the data collected, considering that the Suicidal Risk variable includes four dimensions: Ideation, Family Support, Hopelessness, and Social Isolation. The instruments used were the IDARE questionnaire to assess anxiety and the Suicidal Risk Scale (ERS) to measure suicide risks, both validated for the Colombian population. The main results indicate that both variables present high and moderate levels, although no statistically significant correlations were found in the general scores. However, when analyzing the relationships between the dimensions of suicide risk and anxiety, statistically significant correlations were identified. The study concludes that, while no overall correlation was found, the dimensions of suicide risk suggest a need for a multicausal and integrative analysis. These findings highlight the importance of developing intervention programs involving the school, family, and local authorities.